The Songkran Festival for the Mon Community in Bang Kradii: Social Space to Show Mon Ethnic Identity in the Province of Bangkok. - Anantato, Warisara (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The objective of this study was to analyse the display of Mon ethnic identity at the annual Songkran festival held in Bang Kradii, Bangkok, including analyzing the role it plays for the Mon people in Bang Kradii. The study found that the Mon community of Bang Kradii uses the Songkran festival as a social space to display their ethnic identity through observing various aspects of folklore. These include rituals, clothing and adornments, food, music, stage plays and shows. The Songkran festival facilities the building and passing on the sense of being ethnic Mon, including serving as a center for Mon people and helping of build pride in Mon heritage. It can thus be said that, for the Mon of Bang Kradii, the Songkran festival is a customary device to build Mon social space within Thai society.